Changes induced by recreational and educational activities in children with diabetes - Mercuri, Nora (2009)
Children with diabetes face numerous daily challenges that are completely different from those of other children their age. Dealing with those issues successfully requires that children with diabetes and their families acquire knowledge and develop skills and attitudes to overcome those challenges through a process of continuous education. Such a process simultaneously promotes the development of healthy behavioral changes and the consequent active and effective participation in the control and treatment of the disease.Therapeutic education should start at diabetes diagnosis and should include the child and family members. Residential camps for children and youth with diabetes worldwide appear to be a suitable education strategy because 1) the teaching-learning process is enhanced by a recreational, motivating, and safe environment; 2) the presence of other children and staff members with diabetes give them the opportunity to be in the majority and not an exception; 3) formal education sessions are accompanied by observation, imitation, practice, and exchange of opinions and experience; 4) group creative and innovative didactic methods are useful to convey and consolidate knowledge, self-management, and problem solving skills concerned with diabetes control instead of the traditional passive attitude of the unidirectional educational model,(26–28); and 5) children and their families have the opportunity to integrate and exchange experiences about living with a chronic disease.